The death penalty in contemporary China - Trevaskes, Susan (Palgrave series on Asian governance, 2012)
Killing many and killing fewer -- Deciding guilt -- Sentencing to death -- Choosing life over death -- The turning point -- Shifting narratives of state killing -- Soft-peddling harsh punishment -- Conclusion: life goes on